A simple test method in order to assess the effect of mineral fillers on bitumen ageing. (1st August 2016) - Lesueur, D.; Teixeira, A.; Lázaro, M.M.; Andaluz, D.; Ruiz, A.
Highlights: Mineral filler effect on bitumen ageing was reviewed. Some controversial results arise from experimental differences. A new simple method was therefore proposed. This confirmed the age-reducing effect of hydrated lime. This allowed comparison with other fillers. Abstract: Bitumen has been known to be prone to chemical ageing from the very beginning of its modern use in road construction. It is now well accepted that this results in chemical changes illustrated in particular by an increase in asphaltenes content and in the quantity of functional groups such as sulfoxides and carbonyls. The rheological consequences are a global hardening and embrittlement. However, the role of other potential ingredients of asphalt mixtures on bitumen oxidation kinetics remain poorly documented. If hydrated lime has been observed to reduce ageing for more than 40 years, the role of other mineral fillers is not so clear. Part of the problem comes from the difficulty to use the current standard ageing procedures for bitumen when it comes to mastics (blends of bitumen and filler). The viscosity increase due to the presence of filler decreases the severity of the ageing process in rotating methods such as the celebrated Rolling Thin Film Oven Test (RTFOT). Therefore, we developed a simple procedure based on the existing Pressure Aging Vessel (PAV) and on published equivalence between RTFOT and PAV. This makes it possible to easily quantify the effect of mineral fillers through an increase in ring and ball softening temperature, independent of the viscosity increase due to the filler. Using this method, it is shown that hydrated lime slows down bitumen ageing more than other less active fillers such as hydraulic lime or Portland cement, and that mineral fillers from crushed limestone or granitic aggregate have no effect on bitumen ageing.